Intellectual Origins of the French Enlightenment - Wade, Ira O., 1896-1983 (Book collections on Project MUSE., 1971)
With the same sense of historical responsibility and veracity he has exemplified in his studies on Voltaire, Ira O. Wade turns now to Voltaire's milieu and begins an account of the French Enlightenment which will explain its genesis, its nature and coherence, and its diffusion in the modern world. To understand the movement of ideas that produced the spirit of the Enlightenment, Mr. Wade identifies and examines the people, events, and rich development of philosophy in the Renaissance and seventeenth century. He considers, in turn, the challenges of the Renaissance and the responses of its lea.